2022
DOI: 10.1177/13548565221137002
|View full text |Cite
|
Sign up to set email alerts
|

Social media, migration and the platformization of moral panic: Evidence from Canada

Abstract: As a contentious issue affecting the character, boundaries and future of social order, migration represents a recurrent source of moral panic. While analysts have considered conventional outlets’ role in triggering collective alarm, less is known about social media’s effects on migration’s construction as a social problem. Working with an original dataset of tweets from the 2019 Canadian election, a period of heightened concern and outcry for significant portions of the electorate, this paper employs content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 81 publications
0
1
0
Order By: Relevance
“…Our analysis revealed that the media tries to impose its own vision regarding migrants, either by neglecting them and their needs, or emphasising on negative aspects (the imagological projection of the attacker) by insisting on elements that may cause panic among the general population. The aspect is not new and has been noticed by other researchers in other areas of the world (Walsh & Hill, 2022). Less often, they focus on the struggles that migrants are facing.…”
Section: A Professional Challenge -Media Framing Migrants: From Indif...mentioning
confidence: 99%
“…Our analysis revealed that the media tries to impose its own vision regarding migrants, either by neglecting them and their needs, or emphasising on negative aspects (the imagological projection of the attacker) by insisting on elements that may cause panic among the general population. The aspect is not new and has been noticed by other researchers in other areas of the world (Walsh & Hill, 2022). Less often, they focus on the struggles that migrants are facing.…”
Section: A Professional Challenge -Media Framing Migrants: From Indif...mentioning
confidence: 99%
“…Walsh and Hill advocate for the promotion of counter-narratives that humanise immigrants and challenge stereotypes. 39 Additionally, this paper argues that media literacy programmes can empower individuals to critically analyse media content, discerning between factual reporting and biased narratives. This highlights the pervasive issue of xenophobic languages and immigrants' stereotypical depiction in print media.…”
Section: Presentation Of Findings Xenophobic Languages and Immigrants...mentioning
confidence: 99%